1983
DOI: 10.1128/jvi.48.1.271-280.1983
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of hepatitis B surface antigen in mammalian cells: expression of the entire gene and the coding region

Abstract: We have constructed two simian virus 40 early replacement recombinants that have the coding sequences for hepatitis B virus surface antigen (HBsAg). One construction, LSV-HBsAg, has the coding region for HBsAg but not the portion encoding the putative pre-surface antigen leader. Transformed monkey kidney cells (COS) infected with this recombinant express large quantities of the characteristic partially glycosylated HBsAg molecule, which are assembled into 22-nm particles that appear similar to those produced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0

Year Published

1984
1984
2003
2003

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(43 citation statements)
references
References 32 publications
5
38
0
Order By: Relevance
“…7 B). We and others have shown that HBsAg secreted from SV24 and other transfected cells is particulate, as judged by EM and CsCI: centrifugation (Huovila, A.-P. J., and S. D. Fuller, manuscript in preparation; Dubois et al, 1980;Moriarty et al, 1981;Liu et al, 1982;Laub et al, 1983). This is consistent with the fact that none of the secreted HBsAg entered the gel without reduction (data not shown), indicating all of it was crosslinked in the particles.…”
Section: Time Course Of Particle Formation and Secretionsupporting
confidence: 80%
“…7 B). We and others have shown that HBsAg secreted from SV24 and other transfected cells is particulate, as judged by EM and CsCI: centrifugation (Huovila, A.-P. J., and S. D. Fuller, manuscript in preparation; Dubois et al, 1980;Moriarty et al, 1981;Liu et al, 1982;Laub et al, 1983). This is consistent with the fact that none of the secreted HBsAg entered the gel without reduction (data not shown), indicating all of it was crosslinked in the particles.…”
Section: Time Course Of Particle Formation and Secretionsupporting
confidence: 80%
“…A similar proposal has also been made in the case of the alphaviruses based on the properties of capsid mutants (10), but alphaviruses, in contrast to flaviviruses, bud at the plasma membrane and apparently do not make subviral particles (11). However, secreted subviral particles produced by expression of envelope proteins alone have been reported for hepatitis B virus (27) and the coronavirus mouse hepatitis virus (45), but also in these cases, the exact role of the envelope proteins in the budding mechanism is still unknown.…”
Section: Discussionsupporting
confidence: 56%
“…The results of this experiment show that >95% of the HBsAg synthesized is secreted within a 10 h time period, and that the half-time for secretion is '~3 h. Both p24s and gp27s are released into the medium with similar kinetics. In previous studies, we (18) and others (4,11,13,14) have shown that the material secreted from such transformed cell lines is particulate, as judged by electron microscopy and by equilibrium density centrifugation in CsC1.…”
Section: Resultsmentioning
confidence: 79%